2013
DOI: 10.3329/bccj.v1i1.14361
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Cardiac Emergencies in a Tertiary Care Hospital of Bangladesh

Abstract: Objective: Worldwide cardiac cases constitute a large portion of the medical emergencies. There is a paucity of data on the prevalence of cardiac emergencies in Bangladesh. The purpose of this study was to identify the pattern of presentation of cardiac emergencies in a tertiary care hospital in Bangladesh. Methods and Materials: A hospital based cross sectional study was carried out at a medical college hospital in Dhaka city. Hospital medical records of 2457 patients admitted in the Coronary Care Unit (CCU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…ABM Imam Hosen 1 , Abdul Wadud Chowdhury 2 , Khondker Md. Nurus Sabah 3 , Mohammad GaffarAmin 4 , Mohsin Ahmed 5 , Azizul Haque 6 , Mohammed Nizam Uddin 6 , Biswanath Sarker 7 , Khandaker Abu Rubaiyat 7 , Md. Noor-E-Khuda 1 .…”
Section: Association Of Serum Vitamin D With Acute Myocardial Infarctmentioning
confidence: 99%
See 1 more Smart Citation
“…ABM Imam Hosen 1 , Abdul Wadud Chowdhury 2 , Khondker Md. Nurus Sabah 3 , Mohammad GaffarAmin 4 , Mohsin Ahmed 5 , Azizul Haque 6 , Mohammed Nizam Uddin 6 , Biswanath Sarker 7 , Khandaker Abu Rubaiyat 7 , Md. Noor-E-Khuda 1 .…”
Section: Association Of Serum Vitamin D With Acute Myocardial Infarctmentioning
confidence: 99%
“…This is true for both urban and rural populations and, in men and women, with reported population of prevalence of 70-99%, with severe deficiency (<10 ng/ml) being reported as 62% in studies from Delhi. [4][5][6][7] Another review of vitamin D deficiency in Bangladesh showed prevalence of hypovitaminosis D in Dhaka among 16-40 years women being 12-17% and in Nandail 38-50%. 5 Several mechanisms, direct and indirect, have been proposed for the association of vitamin D with CHD.…”
Section: Association Of Serum Vitamin D With Acute Myocardial Infarctmentioning
confidence: 99%